Polymer-modified liquid crystals - Dierking, Ingo (Royal Society of Chemistry, 2019)
Bridging soft matter physics, materials science and engineering, polymer-modified liquid crystals are an exciting class of materials. They represent a vibrant field of research, promising advances in display technologies, as well as non-display uses. Describing all aspects of polymer-dispersed and polymer-stabilized liquid crystals, the broad coverage of this book makes it a must-have resource for anyone working in the area. The reader will find expert accounts covering basic concepts, materials synthesis and polymerization techniques, properties of various dispersed and stabilized phases, and critical overviews of their applications. Written by leaders in the field, this book provides a state-of-the-art treatment of the topic. It will be essential reading for graduate students, as well as academic and industrial researchers needing an up-to-date guide to the field.- Resumé vydavatel
Keywords: kapalné krystaly; polymery; liquid crystals; polymers; polymerní tekuté krystaly; electronic books; papers of several authors; sborníky; elektronické knihy